PENGASUHAN ANAK USIA 5-6 TAHUN DI KAMPUNG TAPAK LEBARSUMATERA SELATAN 2014 - PUTRA, MANSYUR ROMADON (Program Studi Magister Pendidikan Anak Usia Dini, 2016)
This research aimed conscientious to: (1) Describe fenomena of Tapak Lebar history, (2)Describe aplyed of parenting in Tapak Lebar, (3) Discribe the reason of continuescultureparenting aplyed the regeneration to child labour, (4) Dicribe impact of aplyed parentingresult for unfortunate hold out concerning social behaviour(5) Discribe motoric of child labourresult for unfortunate hold out in Tapak Lebar. Subject in this research are 3 childhood age of 5-6years. This study is qualitative research with ethnographic study of research types. Data analysisused the model Spradley. The research data obtained from observation, documentation, andintervieuw.This findings of this research indicate that (1) Tapak Lebar is fenomena of the place inthere the legand have a biggest sole. (2) The applyed of parenting is hard types and continues forthe regeneration, (3) The reason of parent aplyed parenting to be a hard work childhood,(4)Social behaviour of child labour be over activity.(5)The motoric of child lobour beter strongand agile.